The effect of aerobic exercise on Neurofilament light chain and glial Fibrillary acidic protein level in patients with relapsing remitting type multiple sclerosis - Ercan, Zubeyde; Bilek, Furkan; Demir, Caner Feyzi (Elsevier Sci Ltd, 2021)
Background Multiple sclerosis (MS) is an autoimmune and neurodegenerative disease of the central nervous system in which disease activity can be monitored with some biomarkers. The aim of our study was to investigate serum Glial Fibrillary Acidic Protein (GFAP) and Neurofilament Light Chain (NFL) in relapsing-remitting MS (RRMS) patients after the aerobic exercise. Methods A total of 38 participants with RRMS (Expanded Disability Status Scale: 1.0 - 4.5) were randomized to a study group (3 x /week for 8 weeks at 60 - 70 % of maximal aerobic capacity (VO2max) + home exercises) and a control group (were given home exercises programme 3 times a week for 8 week). Serum NFL and GFAP levels were analyzed using enzyme-linked immunosorbent analysis method before and at the end of 8 weeks. Results: NFL and GFAP levels were statistically lower in the study group at the end of the study than before the study. In the control group, no significant changes were observed in serum NFL and GFAP levels. Delta NFL levels were significantly higher in the study group than control group. Conclusion It was shown, for the first time that serum GFAP and NFL levels (%10 and % 32, respectively) in RRMS patients decreased after aerobic exercise. Our study is important in terms of investigating the effects of aerobic exercise in individuals with RRMS and elucidating the underlying measurable biomarkers. The significant reduction of NFL and GFAP, which have an important role in the pathology associated with nervous system damage in MS, with aerobic exercise may be promising in understanding the regulation of disease activity in MS patients.
Keywords: Glial Fibrillary Acidic Protein; Neurofilament Light Chain; aerobic exercise; multiple sclerosis; biomarker